Working Memory Performance, Pain and Associated Clinical Variables in Women With Fibromyalgia - Gil-Ugidos, Antonio; Rodríguez-Salgado, Dolores; Pidal-Miranda, Marina; Samartin-Veiga, Noelia; Fernández-Prieto, Montse; Carrillo-de-la-Peña, Maria Teresa (Frontiers in Psychology, 2021)
Working memory (WM) is a critical process for cognitive functioning in which fibromyalgia (FM) patients could show cognitive disturbances. Dyscognition in fibromyalgia (FM) has been explained by interference from pain processing, which shares the neural substrates involved in cognition and may capture neural resources required to perform cognitive tasks. However, there is not yet data about how pain is related to WM performance, neither the role that other clinical variables could have. The objectives of this study were 1) to clarify the WM status of patients with FM and its relationship with nociception, and 2) to determine the clinical variables associated to FM that best predict WM performance. To this end, 134 women with FM undertook a neuropsychological assessment of WM functioning (Digit span, Spatial span, ACT tests and a 2-Back task) and a complete clinical assessment (FSQ, FIQ-R, BDI-1A, HADS, PSQI, MFE-30 questionnaires), including determination of pain thresholds by pressure algometry. Patients with FM seem to preserve their WM span and ability to maintain and manipulate information online for both visuospatial and verbal domains. However, up to one-third of patients would show impairment in tasks requiring more short-term memory load, divided attention, and information processing ability. Cognitive performance was spuriously related to the level of pain experienced, finding only that pain measures are related to the ACT task, which measured these same components. Lastly, results suggest that health status, sleep problems and fatigue have a significant influence on WM performance. Future research should take these variables into account when evaluating dyscognition in FM and should include dynamic measures of pain modulation.